Enhanced detection of damaged myocardium and risk stratification in hypertrophic cardiomyopathy using integrated [68Ga]Ga-FAPI-04 PET/CMR imaging. - Ding, Jie; Zhang, Hang; Chen, Xing; Wang, Haiyan; Wang, Weilun; You, Zhiwen; Gao, Liming; Zhang, Qi; Zhao, Jun (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: This study aims to explore the correlation between PET and CMR in integrated [68Ga]Ga-FAPI-04 PET/CMR multimodal imaging and its value in the diagnosis and risk assessment of hypertrophic cardiomyopathy (HCM). Methods: This study included 20 HCM patients and 11 age- and gender-matched controls. PET analysis evaluated left ventricular (LV) [68Ga]Ga-FAPI-04 uptake, including SUVmax, TBR, cardiac fibroblast activity (CFA) and volume (CFV), and total SUV of the 16 segments. CMR tissue characterization parameters included cardiac function, myocardial thickness, late gadolinium enhancement (LGE), relaxation time, extracellular volume (ECV), and peak strain parameters. The 5-year sudden cardiac death (SCD) risk score and the 2-year and 5-year atrial fibrillation (AF) risk scores were calculated for each patient. The study analyzed differences between HCM patients and controls, the correlation between [68Ga]Ga-FAPI-04 PET and concurrent CMR imaging results, and the predictive value of PET/CMR. Result: The FAPI uptake, myocardial mass, myocardial thickness, and T1/T2 mapping values were significantly higher in HCM patients compared to controls. Twenty HCM patients and their 320 myocardial segments were discussed. Increased [68Ga]Ga-FAPI-04 uptake in the left ventricular wall was observed in 95% (19/20) of the patients, covering 48.8% (156/320) of the segments. On concurrent CMR, 80% (16/20) of the patients showed LGE, including 95 (29.7%) segments. The FAPI(+)LGE(+) segments exhibited the highest myocardial PET uptake, greatest thickness, longest T1/T2 native values, largest ECV value and the greatest loss of myocardial strain capacity (P < 0.05). There was a significant correlation between FAPI uptake and CMR parameters (P < 0.05). Higher [68Ga]Ga-FAPI-04 uptake showed a positive correlation with SCD and AF risk scores (P < 0.05). The number of LGE(+) segments, mapping parameters, and ECV values in CMR also had prognostic significance. Combining PET with CMR aided in further risk stratification of HCM. Conclusion: [68Ga]Ga-FAPI-04 PET/CMR multimodal imaging has potential value in the detection of damaged myocardial lesions and risk assessment of HCM patients. [68Ga]Ga-FAPI-04 PET can detect more affected myocardium compared to CMR, and segments with abnormalities in both PET and CMR show more severe myocardial damage.